1999
DOI: 10.1023/a:1007662315835
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The purpose of this study was to determine the correlation between the prevalence of hepatitis C virus (HCV) infection with duration of drug use and other risk factors among drug users. This survey covered 899 male drug users from Kaohsiung Narcotic Abstention Institute and Kaohsiung prison. The prevalence of positive anti-HCV was 67.2% among intravenous drug users (IVDU) and 14.7% among non-intravenous drug users (non-IVDU). Among intravenous (IV) drug users, age and duration of drug use were independently re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Exposure to contaminated blood or blood products, particularly via injection drug use, is the most efficient route of HCV transmission. Among injection drug users in Taiwan in the late 1990s, the prevalence of anti-HCV antibody positivity was 66.4–67.2% [22], [23]. Despite the implementation of national policies aimed at stopping the spread of HCV infection in Taiwan [24], [25], the prevalence of anti-HCV positivity in IDUs with HIV infection in Taiwan was around 97% in the late 2000s [8], [9].…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to contaminated blood or blood products, particularly via injection drug use, is the most efficient route of HCV transmission. Among injection drug users in Taiwan in the late 1990s, the prevalence of anti-HCV antibody positivity was 66.4–67.2% [22], [23]. Despite the implementation of national policies aimed at stopping the spread of HCV infection in Taiwan [24], [25], the prevalence of anti-HCV positivity in IDUs with HIV infection in Taiwan was around 97% in the late 2000s [8], [9].…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies have investigated the seroepidemiology of HCV infection among IDUs in Taiwan [9-11,22-24], none distinguished between HCV mono-infection and HCV infection, and only one evaluated risk factors of HCV infection [11]. Chang et al found that younger age and longer duration of injecting drug use were independently associated with HCV infection among Taiwanese IDUs; however, because that study used a combination of HIV mono-infected and seronegative cases as the reference group, it may have underestimated the effects of HCV infection [11].…”
Section: Discussionmentioning
confidence: 99%
“…Chang et al found that younger age and longer duration of injecting drug use were independently associated with HCV infection among Taiwanese IDUs; however, because that study used a combination of HIV mono-infected and seronegative cases as the reference group, it may have underestimated the effects of HCV infection [11]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rates of HCV infection among past and current IDUs are extremely high generally ranging from 70 % to over 90 % (antibody positive for HCV) in the United States (Chang et al 1999; Williams 1999; Edlin et al 2001). IDUs are frequently involved in the abuse of heroin, one of the most commonly used opiates.…”
Section: Introductionmentioning
confidence: 99%